Application of Python Libraries for real-time data processing: The analysis of social isolation data in the State of Santa Catarina - Vicentainer, Denis (2020)
The need to watch the spread of Covid-19 (Sars-Cov-2) has raised an unprecedented demand for data storage, processing and analysis. This demand imposes on researchers a faster storage, processing and availability of data for viewing by society and public managers. For that, the common data manipulation tools proved to be inefficient in keeping up with the new demands. Considering these factors, this article aims to explore the solution for processing and mapping data from different bases through Python libraries. The Python language has been noted for its variety of libraries aimed at the field of data science, increasing its efficiency as a tool for processing and analyzing data and statistics. To illustrate this process, the treatment of social isolation data in the State of Santa Catarina will be considered between February and May 2020. The text is divided into three parts, in which: i) operational assumptions and installation of libraries; ii) cleaning and analysis of the social isolation data in Santa Catarina and; iii) elaboration of the mapping, generating a map as a product. This test made it possible, in a practical way, to discover and manipulate inconsistencies in the data, resulting in a faster, more assertive product and ready to be made available.